[Afisz. Incipit] Dzień lotnictwa. (Gdańsk : [wydawca nieznany], 1946)
Afisz informujący o dzniu wraz z programem wrzesien 1946 r.
Keywords: Porty lotnicze -- Polska -- Gdańsk -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła